Understanding the ultrasound field of high viscosity mixtures: Experimental and numerical investigation of a lab scale batch reactor - Ariana Bampouli; Quinten Goris; Jonas Van Olmen; Serkan Solmaz; Mohammed Noorul Hussain; Georgios D. Stefanidis; Tom Van Gerven (Ultrasonics Sonochemistry, 2023)
In this work, mixtures of increasing viscosity (from 0.9 to ≈720 mPas) are sonicated directly using an ultrasonic horn at 30 kHz to investigate the effect of viscosity on the ultrasound field both from an experimental and numerical point of view. The viscosity of the mixtures is modified by preparing water-polyethylene glycol solutions. The impact of the higher viscosity on the acoustic pressure distribution is studied qualitatively and semi-quantitatively using sonochemiluminescence. The velocity of light scattering particles added in the mixtures is also explored to quantify acoustic streaming effects using Particle Image Velocimetry (PIV). A numerical model is developed that is able to predict cavitationally active zones accounting for both thermoviscous and cavitation based attenuation. The results show that two cavitation zones exist: one directly under the horn tip and one around the part of the horn body that is immersed in the liquid. The erosion patterns on aluminum foil confirm the existence of both zones. The intensity of the cavitationally active zones decreases considerably with increasing viscosity of the solutions. A similar reduction trend is observed for the velocity of the particles contained in the jet directly under the tip of the horn. Less erratic flow patterns relate to the high viscosity mixtures tested. Finally, two numerical models were made combining different boundary conditions related to the ultrasonic horn. Only the model that includes the radial horn movements is able to qualitatively predict well the location of the cavitation zones and the decrease of the zones intensity, for the highest viscosities studied. The current findings should be taken into consideration in the design and modelling phase of horn based sonochemical reactors.